2020
DOI: 10.1186/s13046-020-01781-x
|View full text |Cite
|
Sign up to set email alerts
|

Dexosomes as a cell-free vaccine for cancer immunotherapy

Abstract: Dendritic cells (DCs) secrete vast quantities of exosomes termed as dexosomes. Dexosomes are symmetric nanoscale heat-stable vesicles that consist of a lipid bilayer displaying a characteristic series of lipid and protein molecules. They include tetraspanins and all established proteins for presenting antigenic material such as the major histocompatibility complex class I/II (MHC I/II) and CD1a, b, c, d proteins and CD86 costimulatory molecule. Dexosomes contribute to antigen-specific cellular immune responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(75 citation statements)
references
References 193 publications
(269 reference statements)
0
75
0
Order By: Relevance
“…For the first time, exosomes, as natural carriers of mRNAand microRNA-, were discovered in mast cells by Valadi et al [14]. Exosomes were also detected as an important carrier of intracellular signaling in several other cells [15,16]. Due to the biocompatibility nature of extracellular vesicles (EVs) with human cells, they successfully cross the cellular membrane and bypass drug delivery obstacles, including RNase degradation, endosomal accumulation, phagocytosis, multidrug resistance, cytotoxicity, and immunogenicity [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…For the first time, exosomes, as natural carriers of mRNAand microRNA-, were discovered in mast cells by Valadi et al [14]. Exosomes were also detected as an important carrier of intracellular signaling in several other cells [15,16]. Due to the biocompatibility nature of extracellular vesicles (EVs) with human cells, they successfully cross the cellular membrane and bypass drug delivery obstacles, including RNase degradation, endosomal accumulation, phagocytosis, multidrug resistance, cytotoxicity, and immunogenicity [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The direct interaction of DEXs with T cells seems to demonstrate poor efficiency in stimulating T cell responses, therefore DEXs have less T cell stimulation potential than their parent DCs (66,84). Some authors suggest that exosomes are not able to interact directly with effector cells, thus prior capturing and processing the exosomes by DCs is a superior pathway of priming specific T cells via DEXs (75,81,85,86). A study using the direct interaction of DEXs with T cells showed that DEXs from mature DCs are better at stimulating T cells than DEXs from immature DCs (87).…”
Section: Exosome-based Vaccines As a Cancer Therapeutic Strategymentioning
confidence: 99%
“…To prime the immune response against a tumor, a specific subset of T-lymphocytes, the CD8 + T-cells, need to be activated. Priming of naïve CD8 + T-cells requires stimulation of the T-cell receptor (TCR) with the antigen-loaded MHCI of the APC and co-stimulation of APC CD80 and CD28 of the naïve CD8 + T-cell [ 507 ]. This results in proliferation of the cytotoxic lymphocyte (CTL).…”
Section: Sevs In Cancer Therapeuticsmentioning
confidence: 99%